Climate Policy after Doha: Turning Obstacles into Solutions - F. J. Radermacher (Cadmus, 2013)
The international climate policy is in big trouble. The governments of the world cannot agree on a reasonable, enforceable cap on global CO2 emissions – not today and not in the future. Concerning a strict enough cap, this issue is politically not handleable today, because this would directly interfere with the options of countries to generate future economic growth. Problems in this respect are politically unfeasible.The present text, therefore, argues for a new approach, for thinking out of the box, for overcoming the traps the negotiations are stuck in at the moment. The idea is to have governments agreeing only on a relaxed instead of a strict cap. This is politically much easier to achieve. In the text, we show that a relaxed cap is sufficient to solve the climate issue, if the private sector can be motivated to do the rest, given that there is an enforceable relaxed cap in place. The private sector can use at least two wild cards to contribute to this aim, and it can do this within the framework of climate neutrality for companies, organizations, and individuals to take legal CO2 certificates out of order on the one hand, and, on the other hand, to plant trees (all over the world for the purpose of biological sequestration) and to do this in huge volumes.